2022
DOI: 10.3390/children9030441
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Radiological Outcome of Combined Femoral and Ilium Osteotomy in Pelvic Reconstruction of the Child

Abstract: Background and Objectives: Reconstruction of the pelvic joint is a common way to address developmental dysplasia of the hip (DDH), as well as neurogenic dislocation of the hip (NDH) and Legg–Calvé–Perthes disease (LCPD) in children. The purpose of this study was to analyze the short-term radiologic outcome after hip reconstructive surgery either treated with sole osteotomy of the femur or in combination with iliac osteotomy in patients with DDH, NDH and LCPD. Materials and Methods: X-rays of 73 children, aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Coxa vara, LLD, limping, overgrowth, and impingement of the greater trochanter are not uncommon among patients who received the operations. To solve the problem, several surgeons ( 14 , 18 , 39 , 40 ) turned to the combined surgery and evaluated the outcomes to prove the effectiveness of this operative design.…”
Section: Discussionmentioning
confidence: 99%
“…Coxa vara, LLD, limping, overgrowth, and impingement of the greater trochanter are not uncommon among patients who received the operations. To solve the problem, several surgeons ( 14 , 18 , 39 , 40 ) turned to the combined surgery and evaluated the outcomes to prove the effectiveness of this operative design.…”
Section: Discussionmentioning
confidence: 99%
“…Combined femoral and innominate osteotomies have been practiced by a few surgeons. [125][126][127][128] Weight-relief. Animal studies have shown that weight-relief does have a beneficial effect on maintaining the shape of the femoral head following induced ischemic necrosis 129 and a few surgeons advocate weight-relief as an adjunct to operative or non-operative containment.…”
Section: Innominate Osteotomy In Many Centers In Northmentioning
confidence: 99%
“…Common surgical procedures for DDH patients include pelvic osteotomy, open reduction, capsular arthroplasty and femoral osteotomy[ 10 ]. To restore the anatomical morphology and mechanical structure of the pelvis and ensure normal development and life of children, pelvic osteotomy is almost inevitable[ 11 , 12 ]. Morphology of the acetabulum after pelvic osteotomy is closely related to prognosis of DDH.…”
Section: Introductionmentioning
confidence: 99%